Management accounting, engineering and the management of company growth: Clarke Chapman, 1864–1914. Issue 2 (June 2015) - McLean, Tom; McGovern, Tom; Davie, Shanta
Abstract: This research examines the relationship between management accounting and engineering in the processes of strategic decision-making and managerial control underlying the management of growth in Clarke Chapman, 1864 – 1914. The research finds that strategic decisions to invest in new technologies were grounded in the engineering ethos of the firm, market awareness and information derived from the firm's extensive business networks. Decisions regarding the (dis)continuance of existing strategic directions were based on management accounting information and product and market awareness. The management and control of costs were important factors underlying significant re-organisations of the firm. Managerial control was exercised on a direct, personal basis and was undertaken in conjunction with the use of routine and ad hoc management accounting reports. The current research makes two major contributions to our knowledge of the development of management accounting. First, it finds that Clarke Chapman's management accounting system evolved incrementally to match the growth requirements of the firm. The research finds no evidence of periodic fluctuations in demand having a significant impact on the development of the management accounting system. Second, the current research indicates that there is no evidence of conflict between professional groupings of engineers and accountants over the ownership of the management accounting system which was rooted in the accounting function. In this respect, it is considered significant that engineering and accounting were both represented at very senior levels in the firm.